Pain in Gynecological Cancer - Patiyus Agustiansyah; Aidyl Fitrisyah; Sartika Nopradilova (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
The International Association for the Study of Pain defines pain as “unpleasant sensory and emotional experiences associated with actual or potential tissue damage.” Pain is common among patients with cancer, with the prevalence of pain being 66.4% in advanced metastatic disease or terminal, 55% during anticancer treatment, 39.3% after curative treatment, and moderate to severe pain were reported in 38.0% of all patients. Pain is one of the most common and dreaded symptoms in cancer sufferers, but the exact number of cancer patients who experience pain is difficult to determine. There are a wide variety of studies in defining pain and the tools they use to measure the complexity of this symptom. Good or complete pain control can be achieved in 80-90% of cancer patients. Nevertheless, despite major advances in pain control, cancer-related pain continues to be a major public health problem globally.